+0  
 
0
82
2
avatar+282 

Confusing help?

lizagame  Mar 1, 2017
Sort: 

2+0 Answers

 #1
avatar
0

C is correct

Guest Mar 1, 2017
 #2
avatar+77149 
0

Length of EF  =   √ [(7 - 1)^2 + (-2 - -2)^2 ]   = √ 6^2   =  6 units

 

Length of E'F' =   12 units

 

Width of FG  = √ [(7 - 7)^2 + (-2 - - 6)^2 ]   = √ 4^2   =  4 units

 

Width of F'G' = 8 units

 

C is correct

 

 

cool cool cool

CPhill  Mar 1, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details